Alignment of Rural Tourism Development in the Special Economic Zone (SEZ): (for Tourism with the Travel and Tourism Development Index (TTDI) Concept in Jatigede, Sumedang) - Ahmad Rimba Dirgantara; Delfta Tunjung Baswarani (Journal of Research on Business and Tourism, 2025)
This research article examines the alignment of rural tourism development in the Jatigede Tourism Special Economic Zone (SEZ) with the Travel and Tourism Development Index (TTDI) indicators. The primary focus of the study is to evaluate the extent to which the SEZ development plan in this region accommodates principles of inclusive, sustainable, and competitive tourism, particularly in the context of villages affected by the construction of the Jatigede reservoir. Using a descriptive, exploratory, and explanatory approach, this study applies the TTDI framework to assess infrastructure, environmental sustainability, human resource capacity, socio-cultural dynamics, and local policy readiness. The findings indicate that the development planning of the Jatigede Tourism SEZ has strong potential to enhance rural tourism; however, further alignment with TTDI standards particularly regarding environmental considerations and local community participation is necessary. The study recommends a collaborative development model involving local governments, village communities, and investors to establish an SEZ that fosters local economic growth while preserving socio-cultural heritage. These recommendations are intended to serve as a strategic reference for policymakers to ensure that implementing the Jatigede Tourism SEZ aligns with TTDI principles and sustainable development goals.